Relevant Aspects Concerning Some Covid-19 Crisis Effects in Romania - Florina POPA; Daniela ANTONESCU; Simona FRONE; Andreea CONSTANTINESCU (Communications of International Proceedings, 2022)
In the context of the COVID-19 pandemic outbreak, requirements of elaboration and implementation of some public policies at world level, emerged, that would counteract the economic consequences of the pandemic crisis. At European States level there were a number of recommendations addressed by International Forums and European Commission, related to the potential of recovery of every country, dependent on their governments¢ capacity to act through efficient policies related to the concrete existent conditions. At national level, the public policies initiated pursued, among others, to avoid the collapse emergence in the Romanian economy and possibilities of recovery, through a number of concrete interventions, at economic and social level. Some effects of the COVID-19 pandemic on the Romanian economy, reflected in macroeconomic indicators, were analyzed. The results express possibilities to return to the potential for economic development prior to the outbreak of the pandemic, under the conditions of continuation of implementation by the government, of some appropriate policies resulting from the programs and plans committed during the pandemic crisis. At the level of European countries and the United Kingdom, an indicator expressing policies initiated by governments, in response to the problems caused by pandemic, was, also, analyzed the results signal active interventions of governmental policies, across all countries, for combat the effects of the pandemic. The paper ends with conclusions and proposals that express the essence of the results obtained. The research methodology used was the documentation from foreign and domestic specialty literature, the analysis of data expressed in macroeconomic indicators and intervention indices, synthesis and processing of information, through the authors’ own interpretation.
Keywords: macroeconomic indicators; pandemic crisis; public policies; index of governments response to pandemic; economic development